O conteúdo da estratégia de produção: uma adaptação para a construção de edificações - Barros Neto, José de Paula (2013)
Building companies are traditionally driven by strategic decision which are mostly based on top managers' intuition and experience. The lack of formal processes for strategic planning often results in a reactive competitive approaches in relation to the environment. Regarding the production function, the operational vision and short-time approach tend to be even more emphasized, sometimes leading to mistakes in investiments that can affect the company financial survival. This paper discusses the formulation of the production strategy in the building industry, emphasizing the adaptation of concepts related to the content of strategic plans. This study is based on case studies carried out in small-sized building companies from the state of Rio Grande do Sul, Brazil.